A Novel UX-Based Approach for Ontology Evaluation: Applying Tree Testing to the Agricultural Product Types Ontology - Filipi Miranda Soares; Antonio Mauro Saraiva; Luis Ferreira Pires; Debora Pignatari Drucker; Kelly Rosa Braghetto; Luiz Olavo Bonino da Silva Santos; Dilvan de Abreu Moreira; Fernando Elias Correa; Alexandre Claudio Botazzo Delbem (IEEE Access)
This paper introduces a novel approach to evaluating ontologies by integrating user experience (UX) metrics, specifically the Tree Testing protocol, into the validation process. Traditional ontology validation often focuses on verifying competency questions via SPARQL queries, overlooking the critical role of domain specialists in assessing usability and conceptual alignment. To address this gap, we applied Tree Testing to the Agricultural Product Types Ontology (APTO), tracking specialists’ navigation paths as they completed 11 domain-specific tasks. This method provided actionable insights into APTO’s usability, revealing structural weaknesses and areas needing refinement. The study involved experts in ontological modeling within the agricultural domain, ensuring feedback was relevant and domain-specific. The findings underscore the value of UX metrics, such as Tree Testing, in identifying user navigation patterns and conceptual misunderstandings. This research illustrates the importance of integrating UX-driven methodologies into ontology design to foster more user-centered and practical knowledge representations for real-world applications. By bridging the gap between technical validation and user-centered evaluation, this work contributes to developing ontologies that are not only technically sound but also intuitive and aligned with the needs of domain experts.